From Polanyi to policy: A tool for measuring embeddedness and designing sustainable agricultural policies - Ament, Joe; Tobin, Daniel; Merrill, Scott C.; Morgan, Caitlin; Morse, Cheryl; Liu, Tung-Lin; Trubek, Amy (Frontiers in Sustainable Food Systems, 2022)
Agricultural systems are deeply enmeshed in complex social processes and institutions, something Polanyi called embeddedness. Designing policy for sustainable agricultural activity requires understanding and measuring such embeddedness. Due to the difficulty of measuring complex social dynamics, however, most policy is aimed at measurable metrics such as price and production. The focus on these metrics imports the rational actor conceptualization of economic activity and fails to incorporate the values, motivations, and socio-cultural components of agricultural decision-making. This paper develops a tool for measuring embeddedness called the Embeddedness Type Matrix (ETM). The tool utilizes survey responses to elucidate economic actors' instrumentalism (decisions motivated by self-interest) and marketness (decisions motivated by market factors). Instrumentalism and marketness are considered together along perpendicular axes to determine the embeddedness quadrant of economic actors. The ETM allows researchers and policy-makers to better understand producers and consumers and design sustainability policies that are aligned with their values and motivations.